1985
DOI: 10.1136/jnnp.48.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Neurological involvement in type 1 (adult) Gaucher's disease.

Abstract: A case of type 1 (adult) Gaucher's disease with a late onset tapeto-retinal degeneration and an initially dopamine responsive extrapyramidal syndrome is described. The literature reporting neurological involvement in type 1 Gaucher's disease is reviewed, and it is concluded that the absence of symptoms and signs of nervous system involvement cannot be used as the sole basis for the classification of this type of Gauchers disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…Conversely, glucocerebrosidase gene mutations have recently emerged as a potential risk factor for idiopathic PD (Aharon-Peretz et al 2004;Bembi et al 2003;Clark et al 2005;Gan-Or et al 2008;Machaczka et al 1999;McKeran et al 1985;Tayebi et al 2003;Ziegler et al 2007). In the largest series of PD patients (in an Israeli Ashkenazi cohort) analyzed for glucocerebrosidase mutations so far (420 PD patients, 333 elderly and 3805 young controls), Gan-Or et al (2008) report that glucerebrosidase mutation carrier frequency is 17.9% in PD patients compared to 4.2% in elderly and 6.4% in young controls.…”
Section: Gd1 and Parkinsonian Symptomsmentioning
confidence: 98%
“…Conversely, glucocerebrosidase gene mutations have recently emerged as a potential risk factor for idiopathic PD (Aharon-Peretz et al 2004;Bembi et al 2003;Clark et al 2005;Gan-Or et al 2008;Machaczka et al 1999;McKeran et al 1985;Tayebi et al 2003;Ziegler et al 2007). In the largest series of PD patients (in an Israeli Ashkenazi cohort) analyzed for glucocerebrosidase mutations so far (420 PD patients, 333 elderly and 3805 young controls), Gan-Or et al (2008) report that glucerebrosidase mutation carrier frequency is 17.9% in PD patients compared to 4.2% in elderly and 6.4% in young controls.…”
Section: Gd1 and Parkinsonian Symptomsmentioning
confidence: 98%
“…However, many patients do not fit into these categories 1 2. Furthermore, the clinical differentiation between GD1 and GD3 is sometimes difficult during the early phase of the disease and patients may have to be reclassified if neurological deficits appear later in life 3. Recently, an epidemiological survey in GD1 patients found that a significant portion had neurological abnormalities 4.…”
mentioning
confidence: 99%
“…In a number of cases these symptoms can be the consequence of secondary complications of the primary disease (e.g. compression of bone marrow or root nerve as a result of vertebral crush fractures caused by osteonecrosis), whereas in other ones they can be the product of specific GBA gene mutations, particularly in patients presenting parkinsonian syndromes (AharonPeretz et al, 2004;Bembi et al, 2003;Clark et al, 2005;Gan-Or et al, 2008;Machaczka et al, 1999;McKeran et al, 1985;Tayeby et al 2003;Ziegler et al 2007). The type 1 GD course is slowly progressive.…”
Section: Fig 1 Involvement β-Glucocerebrosidase In the Catabolic Pamentioning
confidence: 99%